PENGARUH PROMOSI BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA CAPELLA WEDDINGORGINZER - Sri Wulan; Dedi Gumilar (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This research examines the impact of advertising, brand perception, and service excellence on clients' choices when selecting Capella Wedding Organizer services in Bandung. In the fiercely competitive wedding market, understanding the factor that influence consumer choices is crucial for a business’s continued success and expansion.Methods: A qualitative approach was employed, gathering non-numerical data through in-depth interviews with Capella Wedding Organizer clients and potential customers during July 2025.The purposive sampling technique ensured that informants met specific criteria, while data collection involved both direct observation and structured interviews. Analysis classified interview results into narrative descriptions, supplemented by secondary data from scholarly articles to strengthen findings and provide comprehensive insights into the wedding organizer industry dynamics.Results: Digital marketing on platforms such as Instagram, TikTok, and WhatsApp Business effectively raises brand visibility among young adults and Generation Z by utilizing appealing visuals and engaging interactions. A solid brand reputation, formed by business trustworthiness, customer feedback, and a wide range of products, positions Capella as a high-quality service provider. Aspects of service quality—trustworthiness, promptness, confidence, understanding, and physical evidence—play a crucial role in converting potential buyers into customers and fostering customer loyalty through reliable service and personalized care. Keywords: Brand Image, Promotion Strategy, Purchasing Decision, Service Quality, Wedding Organizer